STALZ: Remotely Supporting the Diagnosis, tracking and rehabilitation of patients with Alzheimer's - Hélder Alexandre dos Santos Moreira (2013)
The ever increasing quality in health care led to an impressive improvement of the life expectancy rate in the last decades, which results in an increase in the number of elderly people. Of the diseases associated with aging, Alzheimer's Disease (AD) is one of the most prevalent, representing a rate of up to 80% of all the dementia cases. Due to its symptoms (memory loss, mood changes, disorientation to space, time and people, among others) the disease represents a heavy burden to the patient, the caregiver and the health care system. This comes to show that solutions addressing this topic and that try to improve the current way of tackling the disease are urgent and necessary. The research on the state of the art regarding the current way of handling the disease showed that exist diﬃculties: in obtaining information from the patient periodically; in being able to support the rehabilitation of the patient in a remote environment; in establishing a more permanent contact with the caregiver regarding important events that happen to the patient and can change the disease's progress rate; and, lastly, in having an easy and intuitive way of analyzing the disease's progress. This dissertation addresses these issues by proposing a system capable of: providing the health care professionals with data gathered periodically from the caregiver and the patient; increasing the proximity between the caregiver and the health care professionals; allowing the patient to perform cognitive stimulation exercises in a remote oﬄine environment and by supporting the analysis of the disease's progress by the health care professionals. For the system to be useful, it needed to be designed with its target group in mind. Thereby interfaces were designed according to the existing guidelines when developing for older adults and more specifically, older adults with dementia. These were tested and tuned according to the feedback of the actors relevant to the system (health care professionals, caregivers and patients). The feedback received, regarding the system's usefulness and usability, from the health care professionals and caregivers is positive and the results obtained through the testing of the system are promising.